2016
DOI: 10.1002/app.43824
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and performance of AMPS/AA/DMAA/SA copolymer as a filtrate reducer for oil well cementing

Abstract: A new water‐soluble polymer was prepared and evaluated as a filtrate reducer for oil well cementing. The filtrate reducer (WSP) was synthesized from 2‐acrylamido‐2‐methylpropane sulfonic acid (AMPS), acrylic acid (AA), dimethyl acrylamide (DMAA), and sodium allylsulfonate (SA) by aqueous free radical polymerization. The synthesis conditions were optimized by orthogonal experiment. The molecule structure of the synthesized copolymer (WSP) was verified by Fourier transformer infrared spectrum (FTIR) and nuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Obviously, the different monomer ratio in the polymerization reaction will have a great impact on the polymerization product, thus affecting its performance. However, due to induced decomposition and the cage effect, the amount of initiator has the greatest impact on the free radical polymerization . The order of the influence on the filtration loss is D > A > C > E > B.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Obviously, the different monomer ratio in the polymerization reaction will have a great impact on the polymerization product, thus affecting its performance. However, due to induced decomposition and the cage effect, the amount of initiator has the greatest impact on the free radical polymerization . The order of the influence on the filtration loss is D > A > C > E > B.…”
Section: Resultsmentioning
confidence: 99%
“…The number average molecular weight ( M n ) is 4.7 × 10 5 , the weight average molecular weight ( M w ) is 7.5 × 10 5 , and polydispersity index (PDI) of the prepared sample is 1.811, which indicated that macromolecular polymer have been generated. The relatively high molecular weight and the broad PDI are typical for a radical polymerization . The terpolymer molecular weight and its particle size in solvent have a close relationship.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nowadays, most of FL control additives (filtrate reducer) are water-soluble synthetic polymer products. 6 Tiemeyer and Planck reported that a synthetic polymer based on allyloxy-2-hydroxy propane sulfonic acid exhibited excellent FL performance. 7 Nunes et al synthesized new spherical microparticles.…”
Section: Introductionmentioning
confidence: 99%